Global DNA hypermethylation pattern and unique gene expression signature in liver cancer from patients with Indigenous American ancestry - Cerapio, JP (2021)
Hepatocellular carcinoma (HCC) usually afflicts individuals in their maturity after a protracted liver disease. Contrasting with this pattern, the age structure of HCC in Andean people displays a bimodal distribution with half of the patients developing HCC in adolescence and early adulthood. To deepen our understanding of the molecular determinants of the disease in this population, we conducted an integrative analysis of gene expression and DNA methylation in HCC developed by 74 Peruvian patients, including 39 adolescents and young adults. While genome-wide hypomethylation is considered as a paradigm in human HCCs, our analysis revealed that Peruvian tumors are associated with a global DNA hypermethylation. Moreover, pathway enrichment analysis of transcriptome data characterized an original combination of signatures. Peruvian HCC forgoes canonical activations of IGF2, Notch, Ras/MAPK, and TGF-β signals to depend instead on Hippo/YAP1, MYC, and Wnt/β-catenin pathways. These signatures delineate a homogeneous subtype of liver tumors at the interface of the proliferative and non-proliferative classes of HCCs. Remarkably, the development of this HCC subtype occurs in patients with one of the four Native American mitochondrial haplogroups A-D. Finally, integrative characterization revealed that Peruvian HCC is apparently controlled by the PRC2 complex that mediates cell reprogramming with massive DNA methylation modulating gene expression and pinpointed retinoid signaling as a potential target for epigenetic therapy.